Teenage Mutant Ninja Turtles/Ghostbusters. Volume 4 - Burnham, Erik; Waltz, Tom (Spotlight ; IDW, 2017)
The Ghostbusters and Teenage Mutant Ninja Turtles have one last chance in a battle against Chi-You. In the meantime, Egon and Donatello race against time to fix the Turtles' time machine before it's too late.